Ultrathin films of lignins as a potential transducer in sensing applications involving heavy metal ions - Martins, G. F. [UNESP]; Pereira, A. A. [UNESP]; Straccalano, B. A. [UNESP]; Antunes, P. A.; Pasquini, D.; Curvelo, A. A. S.; Ferreira, M. [UNESP]; Riul, A.; Constantino, C. J. L. [UNESP] (Elsevier B.V. Sa, 2008)
Lignins extracted from sugar cane bagasse using different alcohols in the organosolv-CO(2) supercritical pulping process have been applied in the fabrication of ultrathin films through the Langmuir-Blodgett technique. Langmuir films were characterized by surface pressure versus mean molecular area (Pi-A) isotherms to exploit the sensitivity of nanostructured lignin films to metallic ions (Cu(2+), Cd(2+) and Pb(2+)). The Pi-A isotherms were shifted to larger molecular areas when heavy metal ions are present into the subphase, which might be related to electrostatic repulsions between metallic ions entrapped within the lignin molecular structure. Taking the advantage of metal incorporation, Langmuir monolayers were transferred onto solid substrates forming Langmuir-Blodgett (LB) films to be used as a transducer in an "electronic tongue" system to detect Cu(2+) in aqueous solution below threshold standard established by the Brazilian regulation. Both techniques impedance spectroscopy and electrochemistry have been used in these experiments. Complementary, Fourier transform infrared (FTIR) spectroscopy recorded for LB films before and after soaking into Cu(2+) aqueous solution revealed an interaction between the lignin phenyl groups and the metallic ion. (C) 2007 Elsevier B.V.. All rights reserved.
Keywords: Langmuir-Blodgett films; lignin; sensor; metallic ions